Primary lymphedema precox of the penis and its surgical treatment: a case report - Mıdıoğlu, Haluk; Barutçu, Ali; Karademir, Sacit; Atabey, Atay (The Turkish Journal of Pediatrics, 1992)
Primary penile lymphedema occurs infrequently and is seen in conjunction with a similar process in the scrotum. The accepted form of treatment is surgery since conservative medical treatment is of little value. Different surgical techniques have been described, but no single procedure has emerged as the ideal treatment. Radical excision of all lymphedematous tissues and reconstruction using local penile flaps yield excellent functional and cosmetic results. We treated a 13-year-old boy with primary penile lymphedema precox using radical excision and reconstruction with local penile flaps. At follow-up two years later, functional and cosmetic results were satisfactory.